2020
DOI: 10.1002/pat.4867
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun poly(lactic acid) nanofibers loaded with silver sulfadiazine/[Mg–Al]‐layered double hydroxide as an antimicrobial wound dressing

Abstract: Poly(lactic acid) (PLA) is a versatile, bioabsorbable, and biodegradable polymer with excellent biocompatibility and ability to incorporate a great variety of active agents. Silver sulfadiazine (SDZ) is an antibiotic used to control bacterial infection in external wounds. Aiming to combine the properties of PLA and SDZ, hydrotalcite ([Mg-Al]-LDH) was used as a host matrix to obtain an antimicrobial system efficient in delivering SDZ from electrospun PLA scaffolds intended for wound skin healing. The structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…[74] Carbonate Anion Can be used as an antimicrobial agent [73] Hexazonazole Dual-modal fungicide nanodelivery system, as a fungicide delivery Agent and a micronutrient supplier, to support early plant growth and has the potential to avoid direct contact of fungicides with users due to the intercalation process.…”
Section: Quincloracmentioning
confidence: 99%
See 1 more Smart Citation
“…[74] Carbonate Anion Can be used as an antimicrobial agent [73] Hexazonazole Dual-modal fungicide nanodelivery system, as a fungicide delivery Agent and a micronutrient supplier, to support early plant growth and has the potential to avoid direct contact of fungicides with users due to the intercalation process.…”
Section: Quincloracmentioning
confidence: 99%
“…and inhibit Pseudomonas aeruginosa growth [89] Quinclorac-intercalated LDH is more stable than its free AI form, and can be used as a nanopesticide for rice crop protection [64,74]. Carbonate was used as the guest, and the nanopesticide formed was found to be a better alternative for an antimicrobial agent than its counterpart [73].…”
Section: Cinnamate Anionmentioning
confidence: 99%
“…Conventional burn dressings in second-degree burns [16] Polycaprolactone (PCL)/SSD Electrospinning Antibacterial scaffold [20] P(3HB-co-4HB)/collagen peptide/SSD Aminolysis Potential wound healing [9] Polycaprolactone (PCL) and Polyvinyl alcohol (PVA)/SSD Electrospinning Antimicrobial wound dressing [21] Poly(lactic acid) (PLA)/SSD Electrospinning, structural reconstruction Antimicrobial wound dressing [22] Following the aforementioned background, in the present work, the surface architecture of P(3HB-co-4HB) was enhanced by incorporating collagen peptides and silver sulfadiazine (SSD) as the antimicrobial mechanism agent. Two different scaffolds, namely SSD coat/collagen peptide coat-P(3HB-co-4HB) [SSCC] and SSD blend/collagen peptides coat-P(3HB-co-4HB) [SBCC] scaffold, were fabricated by the combination of salt leaching and freeze-drying techniques which are low cost and apply green technology to fabricate the scaffolds.…”
Section: Biopolymer/materials Fabrication Of Scaffolds Applications Referencesmentioning
confidence: 99%
“…The release study demonstrated half of the loaded THY has been released within 7 h and exhibited good antibacterial potential against Staphylococcus aureus which indicating their use in wound dressing applications [71]. Malafatti and co-workers showcased the preparation of PLA nanofibers containing silver sulfadiazine (SDZ) and hydrotalcite ([Mg-Al]-LDH) which intended for wound skin healing [72]. The kinetics studies revealed slow release of SDZ and also exhibited good inhibitory effects against Escherichia coli and Staphylococcus aureus.…”
Section: Synthetic Polymeric Nanofibers Based Wound Dressingsmentioning
confidence: 99%